Intramuscular triacylglycerol, glycogen and acetyl group metabolism during 4 h of moderate exercise in man - Watt, Matthew J (Blackwell Science Inc, 2002)
This study investigated intramuscular triacylglycerol (IMTG) and glycogen utilisation, pyruvate dehydrogenase activation (PDHa) and acetyl group accumulation during prolonged moderate intensity exercise. Seven endurance-trained men cycled for 240 min at 57 % maximal oxygen consumption (V̇(O2,max)) and duplicate muscle samples were obtained at rest and at 10, 120 and 240 min of exercise. We hypothesised that IMTG utilisation would be augmented during 2-4 h of exercise, while PDHa would be decreased secondary to reduced glycogen metabolism. IMTG was measured on both muscle samples at each time point and the coefficient of variation was 12.3 ± 9.4 %. Whole body respiratory exchange ratio (RER) decreased from 0.89 ± 0.01 at 30 min to 0.83 ± 0.01 at 150 min and remained low throughout exercise. Plasma glycerol and free fatty acids (FFAs) had increased compared with rest at 90 min and progressively increased until exercise cessation. Although plasma glucose tended to decrease with exercise, this was not significant. IMTG was reduced at 120 min compared with rest (0 min, 15.6 ± 0.8 mmol kg(−1) d.m.; 120 min, 12.8 ± 0.7 mmol kg(−1) d.m.) but no further reduction in IMTG was observed at 240 min. Muscle glycogen was 468 ± 49 mmol kg(−1) d.m. at rest and decreased at 120 min and again at 240 min (217 ± 48 and 144 + 47 mmol kg(−1) d.m.). PDHa increased above rest at 10 and 120 min, but decreased at 240 min, which coincided with reduced whole body carbohydrate oxidation. Muscle pyruvate and ATP were unchanged with exercise. Acetyl CoA increased at 10 min and remained elevated throughout exercise. Acetylcarnitine increased at exercise onset but returned to resting values by 240 min. Contrary to our first hypothesis, significant utilisation of IMTG occurred during the first 2 h of moderate exercise but not during hours 2-4. The reduced utilisation of intramuscular fuels during the last 120 min was offset by greater FFA delivery and oxidation. Consistent with the second hypothesis, PDHa decreased late in moderate exercise and closely matched the estimates of lower carbohydrate flux. Although the factor underlying the PDHa decrease was not apparent, reduced pyruvate provision secondary to diminished glycolytic flux is the most likely mechanism.